B-Spline Curve Interpolation Model by using Intuitionistic Fuzzy Approach - Mohammad Izat Emir Zulkifly; Abd. Fatah Wahab; Rozaimi Zakaria (2020)
In this paper, B-spline curve interpolation model by using intuitionistic fuzzy set approach is introduced. Firstly, intuitionistic fuzzy control point relation is defined based on the intuitionistic fuzzy concept. Later, the intuitionistic fuzzy control point relation is blended with B-spline basis function. Through interpolation method, intuitionistic fuzzy B-spline curve model is visualized. Finally, some numerical examples and an algorithm to generate the desired curve is shown.